Mapping the extent and change of gully erosion in the Rosendal region, eastern Free State - Mtembu, Odwa Ntsika (My University, 2022)
Understanding the nature and dynamics of gully systems, and how changes in climatic conditions and land use and land cover might influence gully development is crucial for land management and agricultural practices. Studies on land use and land cover changes have frequently been conducted globally with very few covering detailed changes at a local scale and seldomly integrate the influence of extreme rainfall events in the area. Consequently, many areas experience severe gully erosion within a short or very long period of time with minimal response and effective land management practices to sustain their farming land and protect their livestock. Using remote sensing and the Random Forest algorithm, this study analysed the gully development in Rosendal, eastern Free State in South Africa, and changes with other associated land use and land cover changes from 1975 to 2019. The results showed a total increase of 12% in gulled area and 21% increase in bareland area. The overall accuracies of the six (6) classified images, over the study period ranged from 93.95% to 98.17%, with Kappa co-efficients ranging from 92.94% to 97.88%. The study further determined extreme rainfall events and their influence on gully development in the area from 1945 to 2019. The results showed that the years 1993, 2010 to 2011 and 2016 were the top wettest years, and top driest years being 1981 to 1984 and 2015 to 2016. Since 1945, the years 1993, 2005 to 2006, 2010 to 2013 and 2016 had the most extreme rainfall events associated with increased gullied area, with more gully development coupled with intense extreme high rainfall over a shorter rainfall period in 1993. The increased occurrence of intense rainfall over a shorter rainfall period coupled with drier rainfall periods over a longer period potentially influences the increased gully development in the area. Overall, this study shows mapped and quantified dynamics of gully development and the influence of extreme rainfall events on gully development at a local scale over a short and longer period.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geography, Archaeology & Environmental Studies, University of the Witwatersrand, Johannesburg, 2022